Conhecimento de Geometria de estudantes da Licenciatura em Educação Básica - Menezes, Luís (2014)
This quantitative study aims to assess the development of geometry knowledge of over two hundred students attending Basic Education course in three Schools of Education. Through a test with 21 questions, handed over before and after training in Geometry, students are assessed in a set of categories. The results reveal that although students demonstrate knowledge of elementary concepts at the outset, with percentages of success above 70%, and evolution at the three schools, with an average increase of 5%, also reveal critical aspects related to basic concepts covered in the test.